We12BFit!—Improving Physical Fitness in 7–12-Year-Old Children With Developmental Coordination Disorder: Protocol of a Multicenter Single-Arm Mixed-Method Study - Braaksma, Petra; Stuive, Ilse; van der Hoek, Frouwien D.; van der Sluis, Corry K.; Schoemaker, Marina M.; Dekker, Rienk (Frontiers in Pediatrics, 2018)
Background: Children with developmental coordination disorder (DCD) are less physically fit than their typically developing peers. No substantiated treatments are available for children with DCD to address this issue. Therefore, Aims: This study aims to describe (1) the design and rationale of We12BFit!-PF, a training to increase cardiorespiratory fitness, muscle strength and anaerobic power in 7-12-year-old children with DCD and (2) the methods to examine its preliminary effectiveness and feasibility. Methods: We12BFit!-PF was developed using the steps of defining a treatment theory as proposed by Whyte et al. This includes the definition of targets, mechanisms of action, and essential ingredients. We12BFit!-PF will be evaluated in at least 19 children with DCD aged 7-12, recruited from rehabilitation centers and physical therapy clinics. During the treatment the participants will be engaged in a group training (2 x 60 minutes/ week, 10 weeks) targeting cardiorespiratory fitness using high intensity interval training, muscle strength using exercises without weights and anaerobic power using plyometrics. Training intensity during high intensity interval training will be monitored with heart rate monitors, if necessary the intensity will be adjusted. Using a single-arm mixed-method design, the preliminary effectiveness will be determined using the 20 meter Shuttle Run Test, hand held dynamometry (JAMAR and MicroFET) and the Muscle Power Sprint Test, which will be assessed in week 0, 11 and 23. Feasibility will be assessed by interviewing parents and children and by organizing a focus group session with the trainers at the end of We12BFit!- PF. Ethics and dissemination: The University of Groningen, University Medical Center Groningen medical ethics committee approved the study (METC 2015.216). Final results will be disseminated via scientific publications, presentations and congress proceedings. Funding organizations will receive a final study report. Trial registration: This study was registered with Netherlands Trial Registry (NTR6334, www.trialregister.nl).